THE EFFECT OF PANIC BUYING ON IMPULSE BUYING DURING THE COVID-19 PANDEMIC WITH MUSLIM CONSUMER BEHAVIOR MEDIATORS - Jamilah, Putri; Raskia, Duwita; Putra, Edo Hermawan (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 8 No 1 (2022): The 8th International Conference Of Islamic Economics And Business (ICONIES 2022), 2022)
The phenomenon of the global crisis of the COVID-19 pandemic has an impact on the world's economy and health, triggering a lot of fear, panic, and uncertainty. Panic buying is triggered by difficulties and usually disasters or outbreaks that result in an imbalance between supply and demand, then Impulse buying is a condition that occurs when individuals experience a feeling of urgency and a tendency to buy spontaneously. Unplanned purchases lead to extravagant and excessive behavior this is forbidden in Islam. This study discusses the Effect of Panic Buying on Impulse Buying in the Covid-19 Pandemic Period with Muslim Consumer Behavior Mediator. This research uses descriptive quantitative research methods with SEM PLS analysis with a population of housewives in Pekanbaru as many as 239,948 with a sample of 100 housewives using the sample Slovin. From the results of this study that panic buying on impulse buying has an effect, panic buying on Muslim consumer behavior is the same as impulse buying on Muslim consumer behavior